A kind of high temperature resistant inorganic artificial stone and preparation method thereof
By adding dolomite of specific materials and particle sizes to the inorganic artificial stone substrate and applying a silicon oxide aerogel thermal insulation coating on the surface, the problem of inorganic artificial stone prone to cracking in high temperature environments is solved, and its high temperature resistance and application range are significantly improved.
Patent Information
- Application Number
- CN202310380640.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-04-11
AI Technical Summary
Existing inorganic artificial stones are prone to cracks in high temperature, high salt and high pressure environments, affecting their structural performance and decorative performance, and cannot be widely used in high-temperature environments such as home kitchen countertops, nuclear power plants and other areas.
By adding gradient particle size dolomite, modified white silicate cement, fibers and micropowder to the inorganic artificial stone matrix, and applying a silicon oxide aerogel thermal insulation coating to the surface, the high temperature resistance and crack resistance of the matrix are enhanced.
It significantly improves the flexural strength, tensile strength and high temperature resistance of inorganic artificial stone, extends its application range, and can maintain stability and decorative effects in a high temperature environment of 300-400℃.
Smart Images

Figure CN116444230B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials (IPC classification number is C04B28 / 04), and in particular to a high temperature resistant inorganic artificial stone and a preparation method thereof. Background Art
[0002] Inorganic artificial stone is an artificial stone made of inorganic cementitious materials as bonding materials and calcium carbonate or quartz as aggregates. It has no volatile organic compounds (VOCs), no waste gas, waste liquid, and waste residue emissions during the processing process, low energy consumption for cold processing, and has the advantages of aging resistance, non-combustion, and good decorative performance. It meets the elements of green building materials and will become a new product that attracts attention in the artificial stone industry. In recent years, inorganic artificial stone has been widely used in many squares, shopping malls, subways, airports and other areas in China. However, due to the brittleness of inorganic adhesives themselves, inorganic artificial stone has strict requirements on the application environment. It is easy to crack under high temperature, high salt, and high pressure conditions, affecting its structural and decorative properties. It cannot be used in home kitchen countertops, nuclear power plants, steel mills, bridges and tunnels for the time being.
[0003] Chinese patent CN112897956A discloses an environmentally friendly inorganic artificial stone and a preparation method thereof, wherein quartz sand is replaced by 100 parts of copper tailings and waste concrete, and the artificial stone has excellent performance, simple process and low cost. However, judging from the raw materials used in the preparation, the artificial stone has poor high temperature resistance and is prone to cracking at high temperatures. Chinese patent CN115043617A discloses an artificial stone and a preparation method thereof, wherein the raw materials are mainly copper tailings and waste concrete. The rational use of copper tailings and waste concrete not only protects the environment and reduces environmental pollution, but also eliminates the need to purchase refined filling aggregates required for artificial stone, thereby reducing production costs. Similarly, copper tailings are used as the main filler, and the surface of the copper tailings sand particles is relatively rough, the bite force between the particles is enhanced, and the mechanical strength of the artificial stone is increased, which also means that the brittleness is enhanced and the artificial stone cannot be widely used.
[0004] In this regard, developing a Wuji artificial stone that is resistant to high temperatures and not prone to cracking has extremely high market value. Summary of the invention
[0005] A first aspect of the present invention provides a high temperature resistant inorganic artificial stone, comprising an inorganic artificial stone substrate and a high temperature resistant heat insulating coating coated on the surface of the inorganic artificial stone substrate.
[0006] In some preferred embodiments, the raw materials for preparing the inorganic artificial stone matrix include: aggregate, cement, filler, water reducing agent, coupling agent, thickener, expander, defoamer, and water.
[0007] The applicant discovered during research that adding fillers, coupling agents, and expansion agents simultaneously can improve the strength of the matrix while improving the high temperature resistance of the board.
[0008] In some preferred embodiments, the aggregate includes at least one of dolomite, calcium sand, quartz sand, and tailings sand.
[0009] In some preferred embodiments, the aggregate comprises dolomite. Further, the aggregate comprises dolomite with gradient particle size. Further, the aggregate comprises 20-30 parts of 26-40 mesh dolomite, 25-35 parts of 40-70 mesh dolomite, and 35-55 parts of 70-120 mesh dolomite.
[0010] The dolomite described in the present invention is purchased from the Heling Mineral Products Processing Plant in Lingshou County.
[0011] The applicant has found that by compounding aggregates with gradient particle sizes, not only can the mechanical properties of concrete, especially the flexural strength, be enhanced, but also the water absorption can be reduced.
[0012] In some preferred embodiments, the raw materials for preparing the inorganic artificial stone matrix include, by weight: 45-75 parts of aggregate, 10-30 parts of cement, 5-20 parts of filler, 0.2-2.5 parts of water reducer, 0.1-1 parts of coupling agent, 0.1-1 parts of thickener, 0.5-3 parts of expansion agent, 0.02-0.05 parts of defoamer, and 1-5 parts of water.
[0013] In some preferred embodiments, the cement includes at least one of silicate cement, aluminate cement, sulphoaluminate cement, ferroaluminate cement, fluoroaluminate cement and phosphate cement.
[0014] In order to improve the compatibility of cement in the system, the present invention preferably uses silicate cement, more preferably white silicate cement, specifically any one of metakaolin, slag or silica fume to modify the white silicate cement.
[0015] In order to further improve the material compatibility of artificial stone and reduce water absorption, the white silicate cement has a 28-day flexural strength of 7.5 MPa and an initial setting time of 180 min. It was purchased from Jinan Mingshigang Trading Co., Ltd., specifically Saint-Dehan brand P.W42.5 grade white cement.
[0016] The modification method of white silicate cement comprises: compounding white silicate cement, metakaolin and silica fume in a weight ratio of 10:(1-2):(0.5-1.5), putting into a mixer and mixing evenly, calcining at 890-920° C. for 30 minutes, cooling to room temperature, and passing through a 400-mesh sieve to obtain modified white silicate cement.
[0017] The particle size of the metakaolin is 1250 mesh, which is purchased from Lingshou County Tuyun Mineral Products Processing Plant.
[0018] The silica fume has a particle size of 800 mesh and is purchased from Shandong Minerals.
[0019] In some preferred embodiments, the water reducer includes at least one of high-performance polycarboxylate water reducer, lignin sulfonate water reducer, naphthalene sulfonate water reducer, melamine water reducer, water-soluble resin sulfonate water reducer, aminosulfonate water reducer, and fatty acid water reducer.
[0020] In the system of the present invention, a high-efficiency water reducing agent is used to improve the dispersibility of cement and filler, reduce the water-cement ratio, improve the working performance of materials, further increase the early mechanical strength of the board, and improve the working performance of materials.
[0021] In some preferred embodiments, the thickener includes at least one of hydroxycellulose ether, hydroxymethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, propyl methyl cellulose, and hydroxyethyl cellulose.
[0022] In some preferred embodiments, the defoaming agent includes at least one of tributyl phosphate, polyacrylate, linear polysiloxane, and polyether-siloxane copolymer.
[0023] In some preferred embodiments, the expansion agent includes at least one of a calcium oxide expansion agent, a magnesium oxide expansion agent, a calcium sulfoaluminate expansion agent, and a calcium sulfoaluminate-calcium oxide composite expansion agent.
[0024] The expansion agent is used to generate prestress in the board at an early stage (standard curing for 1-3 days). The release of prestress when the board is heated in the later stage can offset the thermal stress generated by the different expansion coefficients of the components inside the board. According to tests, when the expansion agent is added in an amount of 1-3 parts, the prestress of the board can be controlled within an appropriate range, which can not only avoid damaging the internal structure of the board, but also improve the high temperature resistance of the board.
[0025] In some preferred embodiments, the filler includes fibers and micro powders with a mesh size of 200 or more.
[0026] Furthermore, the weight ratio of the fiber to the micropowder is (0.1-2):(5-15).
[0027] Furthermore, the fiber includes at least one of glass fiber, carbon fiber, steel fiber, and polypropylene fiber.
[0028] Furthermore, the micropowder includes at least one of glass microbeads, expanded perlite, and basalt.
[0029] The applicant has found that the compound addition of fiber and micropowder can significantly reduce the thermal conductivity of the board and improve the high temperature resistance of the board. The spherical and fibrous structures can form a large number of tiny pores in the slurry, eliminate part of the concentrated stress, resist the expansion of cracks, improve the fracture toughness of the board, and further improve the strength and toughness of the board. In particular, when the fiber addition amount is 0.2-1.5 parts, the flexural strength and tensile strength of the board can be significantly improved, and the material mixing efficiency and the decorative effect of the board are basically not affected.
[0030] The present invention does not impose any particular limitation on the coupling agent, which can be selected from silane coupling agents, including but not limited to KH550, KH560, and KH570.
[0031] In some preferred embodiments, the raw materials for preparing the high temperature resistant thermal insulation coating include: at least one of silica aerogel and zirconia aerogel. In order to improve the thermal insulation effect and compatibility with the plate material, the raw material for preparing the high temperature resistant thermal insulation coating is silica aerogel.
[0032] The preparation method of silica aerogel is as follows: according to the mass ratio, tetraethyl orthosilicate (TEOS) and deionized water are mixed evenly on a magnetic stirrer, hydrochloric acid is added to adjust the pH value to 2-3, and after sufficient stirring, ammonia water is continued to be added dropwise to adjust the pH value to 5-6 to produce gel, which is transferred to anhydrous ethanol and aged for 2-3 days for hydrophobic modification. The obtained gel is dried by supercritical carbon dioxide to become SiO2 aerogel, and its thermal conductivity is measured to be 0.015-0.025W / (m·k).
[0033] In order to further isolate the heat source and increase the high temperature resistance and heat non-conductivity, the thickness of the silicon oxide aerogel is 0.5-3 mm.
[0034] The second aspect of the present invention provides a method for preparing a high temperature resistant inorganic artificial stone, comprising the following steps:
[0035] S1. The aggregate, filler, expansion agent and cement are mixed and stirred to obtain a mixture A;
[0036] S2. The water, water reducing agent, coupling agent and defoaming agent are stirred and evenly added to the mixture A to obtain a mixture B;
[0037] S3. Add the thickener to the mixture B and stir to obtain a mixture C;
[0038] S4. The mixture C is poured in layers in a mold, and after demoulding, it is cured, and a high-temperature resistant heat-insulating coating is coated on its surface to obtain a high-temperature resistant inorganic artificial stone.
[0039] In S4, the mixture C is poured in layers in the mold, and a layer of fiber mesh is evenly laid on the surface of each layer of material until the pouring is completed. After demolding, the inorganic product is subjected to standard curing for 7 days, and a high-temperature resistant heat-insulating coating is coated on its surface, and cured for 14 days to obtain a high-temperature resistant inorganic artificial stone.
[0040] Furthermore, the thickness of the high temperature resistant heat insulating coating applied on the surface of the board is 0.5-3mm, and it needs to be cured for 12-48 hours after coating before use.
[0041] Furthermore, the mixture C is poured in layers in a mold, with a layer height of ≥5 mm, and the fiber mass of each layer accounts for 0.05-0.2% of the total mass of the material.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] 1. The simultaneous addition of filler, coupling agent and expansion agent in the present invention can form chemical bonds between cement gelling products and fibers, which can enhance the bonding force between fibers, aggregates and cement, improve the flexural strength and toughness of the board, and resist high-temperature deformation and cracking of the board. The addition of thickener makes the board have higher membrane strength and adhesion, which can improve the density of the board and the working performance of the board.
[0044] 2. The present invention uses multi-layer fiber fabrics to form a fiber net inside the board, which improves the tensile performance of the board, and the light aggregate in the filler can effectively alleviate the stress concentration effect, making the board structure stable and not easy to crack under high temperature conditions. The expansion agent can generate tensile stress inside the board, and reduce the compressive stress caused by the uneven thermal expansion coefficient of the internal aggregate and cementitious material under high temperature conditions; the aerogel has a low thermal conductivity, which can effectively isolate the external heat from being transferred to the board, and improve the high temperature resistance of the board.
[0045] 3. The surface heat-resistant temperature of the inorganic artificial stone in the prior art is about 100°C, while the surface heat-resistant temperature of the inorganic artificial stone prepared by the present invention can reach 300-400°C, which broadens the application scope of the inorganic artificial stone.
[0046] 4. The present invention modifies silicate cement of specific strength by using kaolin and silica fume of specific particle size. The obtained modified white silicate cement has poor dispersibility such as no material agglomeration. The artificial stone material prepared has good compatibility and low water absorption, and is particularly suitable for household kitchen countertops.
[0047] 5. The silica aerogel prepared by the present invention has good heat insulation effect on the one hand, and solves the problem of poor interface compatibility between colloidal materials and cement materials, especially easy cracking when heated, so that the artificial stone has stronger high temperature resistance and is durable. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a photo of the inorganic artificial stone prepared in Example 1;
[0049] Figure 2 This is a photo of the inorganic artificial stone prepared in comparison sample 1. DETAILED DESCRIPTION
[0050] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Example 1
[0052] A first aspect of the present embodiment provides a high temperature resistant inorganic artificial stone, comprising an inorganic artificial stone substrate and a high temperature resistant heat insulating coating coated on the surface of the inorganic artificial stone substrate.
[0053] By weight, the raw materials for preparing the inorganic artificial stone matrix include: 65 parts of aggregate, 25 parts of cement, 5.2 parts of filler, 1 part of water reducer, 0.2 parts of coupling agent, 0.2 parts of thickener, 0.5 parts of expansion agent, 0.03 parts of defoamer and 3 parts of water.
[0054] The aggregate is 20 parts of 26-40 mesh dolomite, 25 parts of 40-70 mesh dolomite, and 35 parts of 70-120 mesh dolomite;
[0055] The cement is modified white silicate cement, and the preparation method comprises:
[0056] White silicate cement, metakaolin and silica fume are compounded in a weight ratio of 10:2:1.5, put into a mixer and mixed evenly, calcined at 890°C for 30 minutes, cooled to room temperature, and passed through a 400-mesh sieve to obtain modified white silicate cement.
[0057] The filler is a compound of 200 mesh basalt micropowder and glass fiber in a weight ratio of 5:0.2; the water reducer is the 140 type polycarboxylate water reducer produced by the Institute of Building Science; the coupling agent is KH560; the thickener is hydroxyethyl methyl cellulose; the expansion agent is the TD-P1 type calcium sulfoaluminate expansion agent produced by Taino Building Materials; and the defoamer is the THIX-5682 type concrete defoamer produced by Hengxin Chemical.
[0058] A second aspect of the present embodiment provides a method for preparing a high temperature resistant inorganic artificial stone, comprising the following steps:
[0059] S1. Mix the aggregate, filler, expansion agent and cement, stir at 120r / min for 3min until uniform, and stir evenly to obtain mixture A;
[0060] S2. Add water, water reducing agent, coupling agent and defoaming agent to mixture A, stir at a slow speed of 80 r / min for 2 min to mix evenly, and then stir at a high speed of 400 r / min for 5 min to obtain mixture B;
[0061] S3. Add the thickener to the mixture B and stir at a high speed of 400 r / min for 2 min to obtain a mixture C;
[0062] S4. The mixture C was poured in layers in the mold, and each layer of material was evenly laid on its surface with a layer of fiber mesh, with a layer height of 5mm, until the pouring was completed, the poured slurry was placed in a vacuum vibration press, the vacuum degree was -0.09MPa, and the vacuum was evacuated for 5min to obtain an inorganic artificial stone. After curing for 7 days, the surface was sprayed with silica aerogel to obtain a high temperature resistant heat insulating coating with a thickness of 1.2mm, and the high temperature resistant inorganic artificial stone was obtained after curing for 14 days;
[0063] The preparation method of the silicon oxide aerogel is as follows: tetraethyl orthosilicate (TEOS) and deionized water are mixed evenly in a magnetic stirrer in a mass ratio of 1:10, hydrochloric acid is added to adjust the pH value to 2, and after sufficient stirring, ammonia water is continuously added dropwise to adjust the pH value to 5-5.5 to produce gel, which is transferred to anhydrous ethanol and aged for 2 days for hydrophobic modification. The obtained gel is dried by supercritical carbon dioxide to form SiO2 aerogel, and its thermal conductivity is measured to be 0.02W / (m·k).
[0064] Example 2
[0065] A first aspect of the present embodiment provides a high temperature resistant inorganic artificial stone, comprising an inorganic artificial stone substrate and a high temperature resistant heat insulating coating coated on the surface of the inorganic artificial stone substrate.
[0066] By weight, the raw materials for preparing the inorganic artificial stone matrix include: 60 parts of aggregate, 28 parts of cement, 7.3 parts of filler, 1.2 parts of water reducer, 0.25 parts of coupling agent, 0.3 parts of thickener, 0.7 parts of expansion agent, 0.02 parts of defoamer and 3.5 parts of water.
[0067] The aggregate is 20 parts of 26-40 mesh dolomite, 30 parts of 40-70 mesh dolomite, and 55 parts of 70-120 mesh dolomite;
[0068] The cement is modified white silicate cement, and the preparation method comprises:
[0069] The silicate cement, metakaolin and silica fume are compounded in a weight ratio of 10:1.5:1, put into a mixer and mixed evenly, calcined at 900°C for 30 minutes, cooled to room temperature, and passed through a 400-mesh sieve to obtain modified silicate cement.
[0070] The filler is a compound of 325 mesh glass beads and carbon fibers in a weight ratio of 7:0.3; the water reducer is the 140 type polycarboxylate water reducer produced by the Institute of Building Science; the coupling agent is KH550; the thickener is methyl cellulose; the expansion agent is the UEA expansion agent produced by Taino Building Materials; and the defoamer is the THIX-5682 concrete defoamer produced by Hengxin Chemical.
[0071] A second aspect of the present embodiment provides a method for preparing a high temperature resistant inorganic artificial stone, comprising the following steps:
[0072] S1. Aggregate, filler, expansion agent and cement were mixed and stirred at 70 r / min for 4 min until uniform, and mixture A was obtained by stirring uniformly;
[0073] S2. Add water, water reducing agent, coupling agent and defoaming agent to mixture A, stir at a slow speed of 90 r / min for 1 min to mix evenly, and then stir at a high speed of 400 r / min for 6 min to obtain mixture B;
[0074] S3. Add the thickener to the mixture B and stir at 350 r / min for 3 min to obtain a mixture C;
[0075] S4. The mixture C was poured in layers in the mold, and each layer of material was evenly laid on its surface with a layer of fiber mesh, with a layer height of 5mm, until the pouring was completed, the poured slurry was placed in a vacuum vibration press, the vacuum degree was -0.09MPa, and the vacuum was evacuated for 6min to obtain an inorganic artificial stone. After curing for 7 days, the surface was sprayed with zirconia aerogel to obtain a high temperature resistant heat insulating coating with a thickness of 1.6mm, and the high temperature resistant inorganic artificial stone was obtained after curing for 14 days;
[0076] The preparation method of the silicon oxide aerogel is as follows: tetraethyl orthosilicate (TEOS) and deionized water are mixed evenly in a magnetic stirrer in a mass ratio of 1:8, hydrochloric acid is added to adjust the pH value to 2, and after sufficient stirring, ammonia water is continuously added dropwise to adjust the pH value to 5-5.5 to produce gel, which is transferred to anhydrous ethanol and aged for 3 days for hydrophobic modification. The obtained gel is dried by supercritical carbon dioxide to form SiO2 aerogel, and its thermal conductivity is measured to be 0.015W / (m·k).
[0077] Example 3
[0078] A first aspect of the present embodiment provides a high temperature resistant inorganic artificial stone, comprising an inorganic artificial stone substrate and a high temperature resistant heat insulating coating coated on the surface of the inorganic artificial stone substrate.
[0079] By weight, the raw materials for preparing the inorganic artificial stone matrix include: 55 parts of aggregate, 24 parts of cement, 12.3 parts of filler, 1.2 parts of water reducer, 0.25 parts of coupling agent, 0.3 parts of thickener, 0.7 parts of expansion agent, 0.02 parts of defoamer and 5 parts of water.
[0080] The aggregate is 40 parts of 26-40 mesh dolomite, 20 parts of 40-70 mesh dolomite, and 35 parts of 70-120 mesh dolomite;
[0081] The cement is modified white silicate cement, and the preparation method comprises:
[0082] The silicate cement, metakaolin and silica fume were compounded in a weight ratio of 10:1:1, put into a mixer and mixed evenly, calcined at 910°C for 30 minutes, cooled to room temperature, and passed through a 400-mesh sieve to obtain modified silicate cement.
[0083] The filler is a compound of 300 mesh expanded perlite micropowder and polypropylene fiber in a weight ratio of 12:0.3; the water reducer is the 140 type polycarboxylate water reducer produced by the Institute of Building Science; the coupling agent is KH570; the thickener is hydroxypropyl methylcellulose; the expansion agent is the TD-P1 type calcium sulfoaluminate expansion agent produced by Tyno Building Materials; and the defoamer is the THIX-5682 type concrete defoamer produced by Hengxin Chemical.
[0084] A second aspect of the present embodiment provides a method for preparing a high temperature resistant inorganic artificial stone, comprising the following steps:
[0085] S1. Aggregate, filler, expansion agent and cement were mixed and stirred at 80 r / min for 6 min until uniform, and mixture A was obtained by stirring uniformly;
[0086] S2. Add water, water reducing agent, coupling agent and defoaming agent to mixture A, stir at a slow speed of 120 r / min for 3 min to mix evenly, and then stir at a high speed of 380 r / min for 3 min to obtain mixture B;
[0087] S3. Add the thickener to the mixture B and stir at 350 r / min for 3 min to obtain a mixture C;
[0088] S4. The mixture C was poured in layers in the mold, and each layer of material was evenly laid on its surface with a layer of fiber mesh, with a layer height of 10 mm, until the pouring was completed, the poured slurry was placed in a vacuum vibration press, the vacuum degree was -0.09 MPa, and the vacuum was evacuated for 3 min to obtain an inorganic artificial stone. After curing for 7 days, the surface was sprayed with silica aerogel to obtain a high temperature resistant heat insulating coating with a thickness of 2.0 mm, and the high temperature resistant inorganic artificial stone was obtained after curing for 14 days;
[0089] The preparation method of the silicon oxide aerogel is as follows: tetraethyl orthosilicate (TEOS) and deionized water are mixed uniformly in a magnetic stirrer in a mass ratio of 1:13, hydrochloric acid is added to adjust the pH value to 2, and after sufficient stirring, ammonia water is continuously added dropwise to adjust the pH value to 5-5.5 to produce gel, which is transferred to anhydrous ethanol and aged for 3 days for hydrophobic modification. The obtained gel is dried by supercritical carbon dioxide to form SiO2 aerogel, and its thermal conductivity is measured to be 0.025W / (m·k).
[0090] Comparative Example 1
[0091] The first aspect of this comparative example provides a high temperature resistant inorganic artificial stone. The specific implementation method is the same as that of Example 1, except that, by weight, the raw materials for preparing the inorganic artificial stone matrix include: 55 parts of aggregate, 40 parts of cement, 2 parts of filler, 0.2 parts of water reducer, 0.03 parts of defoamer, and 3 parts of water.
[0092] The cement is common commercially available white cement; the filler is 200-mesh basalt powder.
[0093] The second aspect of this comparative example provides a method for preparing a high temperature resistant inorganic artificial stone, comprising the following steps:
[0094] S1. Aggregate, cement and filler were stirred at 50r / min for 3min until they were uniform to obtain mixture A;
[0095] S2. Add water, water reducing agent and defoaming agent to the mixture A during stirring, stir at a slow speed of 100 r / min for 2 min to mix evenly, and then stir at a high speed of 420 r / min for 3 min to obtain mixture B;
[0096] S3. Mixture B is poured into a mold, cured for 7 days, and a silicon oxide aerogel is sprayed on the surface to obtain a high-temperature resistant heat-insulating coating with a thickness of 1.5 mm. The high-temperature resistant inorganic artificial stone is obtained by curing for 14 days.
[0097] The preparation method of the silicon oxide aerogel is the same as Example 1.
[0098] Comparative Example 2
[0099] The first aspect of this comparative example provides a high temperature resistant inorganic artificial stone, and the specific implementation manner is the same as that of Example 1, except that the aggregate is calcium sand.
[0100] The second aspect of this embodiment provides a method for preparing a high temperature resistant inorganic artificial stone, and the specific implementation method is the same as that of the embodiment.
[0101] Comparative Example 3
[0102] The first aspect of this comparative example provides a high temperature resistant inorganic artificial stone, and the specific implementation manner is the same as that of Example 1, except that the aggregate is 25 parts of 40-70 mesh dolomite and 35 parts of 70-120 mesh dolomite.
[0103] The second aspect of this embodiment provides a method for preparing a high temperature resistant inorganic artificial stone, and the specific implementation method is the same as that of the embodiment.
[0104] Comparative Example 4
[0105] The first aspect of this comparative example provides a high temperature resistant inorganic artificial stone, and the specific implementation method is the same as that of Example 1.
[0106] The second aspect of this embodiment provides a method for preparing a high temperature resistant inorganic artificial stone. The specific implementation method is different from the embodiment in that zirconium oxide aerogel (purchased from Nano Technology) is used to replace silicon oxide aerogel.
[0107] Performance Testing
[0108] The inorganic artificial stones produced in the above embodiments and comparative examples were tested, and the test results are shown in Table 1.
[0109] The flexural strength and water absorption rate are tested according to GB / T 35157-2017 standard;
[0110] The surface heat resistance temperature detection method is as follows:
[0111] The electric heating table is set to a fixed temperature, and a 300*300*20mm wooden board is placed on the table top. A hole (200mm in diameter) is dug in the middle of the wooden board. Then the test board 300*300*20mm is placed on the wooden board, and the electric heating table is continuously heated (50℃-400℃) at a heating rate of 10℃ / min. Strain gauges are attached to the side of the board to record the temperature at which cracks appear in the board. Five boards are selected from each group for testing, and the average surface heat resistance temperature of the five boards is calculated as the final heat resistance temperature of the board.
[0112] Table 1. Performance indexes of inorganic artificial stone
[0113]
[0114]
[0115] From the above results, it can be seen that the embodiments have high strength and apparent density, and good high temperature resistance; from comparative example 1, it can be seen that the product without the raw materials and process of the present invention has low strength and poor high temperature resistance; from comparative examples 2-3, it can be seen that the specific aggregate of the present invention is used, the flexural strength is significantly reduced, and the water absorption rate is affected. In comparative example 4, commercially available zirconium oxide aerogel is used, and the thermal insulation effect is reduced, and the mechanical effect and water absorption are also affected. Among them, the inorganic artificial stone prepared in Example 1 is as follows Figure 1 As shown, in Comparative Example 1, inorganic artificial stone is prepared as Figure 2 shown.
[0116] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high temperature resistant inorganic artificial stone, characterized in that: It comprises an inorganic artificial stone substrate and a high temperature resistant heat insulating coating coated on the surface of the inorganic artificial stone substrate; In parts by weight, the raw materials for preparing the inorganic artificial stone matrix include: 60 parts of aggregate, 28 parts of cement, 7.3 parts of filler, 1.2 parts of water reducer, 0.25 parts of coupling agent, 0.3 parts of thickener, 0.7 parts of expansion agent, 0.02 parts of defoamer, and 3.5 parts of water; The aggregate is 20 parts of 26-40 mesh dolomite, 30 parts of 40-70 mesh dolomite, and 55 parts of 70-120 mesh dolomite; The cement is modified white silicate cement, and the preparation method comprises: compounding silicate cement, metakaolin and silica fume in a weight ratio of 10:1.5:1, putting into a mixer and mixing evenly, calcining at 900°C for 30 minutes, cooling to room temperature, and passing through a 400-mesh sieve to obtain modified silicate cement; The 28-day flexural strength of the silicate cement is 7.5 MPa and the initial setting time is 180 min; The filler is a mixture of 325 mesh glass micro beads and carbon fibers in a weight ratio of 7:0.3; The raw material for preparing the high-temperature resistant heat-insulating coating is silicon oxide aerogel. The preparation method of silicon oxide aerogel is as follows: according to the mass ratio, 1:8 of tetraethyl orthosilicate and deionized water are mixed evenly on a magnetic stirrer, hydrochloric acid is added to adjust the pH value to 2, and after sufficient stirring, ammonia water is continuously added dropwise to adjust the pH value to 5-5.5 to produce gel, which is transferred to anhydrous ethanol and aged for 3 days for hydrophobic modification. The obtained gel is dried into SiO2 aerogel by supercritical carbon dioxide, and its thermal conductivity is measured to be 0.015W / (m·k).
2. The high temperature resistant inorganic artificial stone according to claim 1, characterized in that: The defoaming agent includes at least one of tributyl phosphate, polyacrylate, linear polysiloxane, and polyether-siloxane copolymer.
3. The high temperature resistant inorganic artificial stone according to claim 1, characterized in that: The expansion agent includes at least one of a calcium oxide expansion agent, a magnesium oxide expansion agent, a calcium sulfoaluminate expansion agent, and a calcium sulfoaluminate-calcium oxide composite expansion agent.
4. A method for preparing a high temperature resistant inorganic artificial stone according to any one of claims 1 to 3, characterized in that: The steps include: S1. The aggregate, filler, expansion agent and cement are mixed and stirred to obtain a mixture A; S2. The water, water reducing agent, coupling agent and defoaming agent are stirred and evenly added to the mixture A to obtain a mixture B; S3. Add the thickener to the mixture B and stir to obtain a mixture C; S4. The mixture C is poured in layers in a mold, and after demoulding, it is cured, and a high-temperature resistant heat-insulating coating is coated on its surface to obtain a high-temperature resistant inorganic artificial stone.
Citation Information
Patent Citations
Environment-friendly inorganic artificial stone and preparation method thereof
CN112897956A
Artificial stone and preparation method thereof
CN115043617A
Early-strength high-temperature-resistant sleeve grouting material and preparation method thereof
CN112745093A
Dry mixing material for square stock type inorganic artificial stone, inorganic artificial stone and preparation method
CN114276096A